Code-mixing between Skolt Saami Neiden dialect and Sea Saami - Markus, Juutinen (Puhe ja kieli, 2019)
In this paper I study code-mixing between Skolt Saami Neiden dialect and North Saami Sea Saami dialect. The material I use contains texts from two bilingual speakers collected in Neiden Norway in year 1920. The collector Eliel Lagercrantz describes some of the texts as Sea Saami and the others as mixed language of Skolt Saami and Sea Saami. In the study I found out that the texts contain three different registers: Sea Saami, Skolt Saami, and a register I call as Skolt Saami-Sea Saami. Skolt Saami and Sea Saami registers contain short insertions from other language. The Skolt Saami-Sea Saami register contain both grammar and vocabulary from both languages. I call this as conguent lexicalization which means that a speaker can fill the grammatical stuctures shared by the languages with the vocabulary of Skolt Saami and North Saami. In the study I also found out that the texts contain hybrid wordforms. Phonetical hybrid forms have phonetical features from both languages. In grammatical hybrid forms a word from one language is conjugated in the other language. Tässä artikkelissa tutkin koltansaamen Näätämön murteen ja pohjoissaamen merisaamen murteen välistä koodien sekoittumista. Tutkimusaineistona käytän kahdelta kaksikieliseltä puhujalta vuonna 1920 Norjan Näätämössä kerättyjä folkloretekstejä. Aineiston kerääjän Eliel Lagercrantzin mukaan osa teksteistä on merisaamea ja osan kieltä hän kuvailee termillä koltansaamen ja merisaamen sekakieli. Tutkimuksessa selvisi, että tekstit sisältävät kolme erilaista rekisteriä: koltansaame, merisaame sekä rekisteri, jota kutsun koltansaame-merisaame -rekisteriksi. Kaksi ensimmäistä rekisteriä sisältävät lyhyitä koodinupotuksia toisesta kielestä. Koltansaame-merisaame -rekisteri sisältää sekä kielioppia että sanastoa molemmista kielistä. Kutsun tätä kongruentiksi leksikalisaatioksi. Koska kielet ovat lähisukukieliä ja jakavat sekä perussanaston että paljon yhteisiä kieliopillisia rakenteita, puhuja voi täyttää kielten yhteiset kieliopilliset rakenteet molempien kielten ...